PENGEMBANGAN DESA WISATA MELALUI PELATIHAN DIGITAL MARKETING DALAM MENINGKATKAN UMKM DESA MADIASARI - Febriansyah, Febriansyah; Ramadhanti, Manda; Novyantari, Zahrani Tri; Rustandi, Dede; Hamdan, Ahmad (CV Bayfa Cendekia Indonesia Bekerjasama dengan Jurusan/Program Studi Pendidikan Masyarakat FKIP Universitas Siliwangi, 2024)
Madiasari Village is a pilot tourism village located in Cineam District, Tasikmalaya Regency where there are several potentials ranging from religious tourism, cultural tourism, to nature tourism, and even local micro, small and medium business centers such as crafts and food. There are several obstacles that cause all these sectors not to be optimized, starting from the lack of public awareness of the local potential owned and not understanding the community about marketing micro, small and medium business products in digital marketing. The purpose of the implementation of this digital marketing training is to help the community, especially micro, small and medium enterprises in marketing their products digitally in order to get a wider market and introduce local products in Madisari Village. In this Digital Marketing Training activity using the social demand approach method and integrative approach. The result of this digital marketing training is that the Madiasari Village community understands the strategies in marketing their products digitally in order to get a wider market.